2006
DOI: 10.1093/europace/eul062
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years of paediatric cardiac pacing: 515 pacemakers and 480 leads implanted in 292 patients

Abstract: Pacing in children shows good results, but complications are frequent and related to leads. Endocardial pacing showed better long-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
71
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 19 publications
6
71
1
1
Order By: Relevance
“…The 5-year epicardial lead survival was 74% [4]. Similar findings were reported by Silvetti et al They described failure in 21% of the children who received in total 226 epicardial leads during a mean follow-up of 5 years [5]. In our study lead failure occurred in 15% of the implanted epicardial leads.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The 5-year epicardial lead survival was 74% [4]. Similar findings were reported by Silvetti et al They described failure in 21% of the children who received in total 226 epicardial leads during a mean follow-up of 5 years [5]. In our study lead failure occurred in 15% of the implanted epicardial leads.…”
Section: Discussionsupporting
confidence: 88%
“…However, in the presence of (relative) contraindications for the transvenous approach, such as small body size, an intra-cardiac shunt or absence of a venous access, an epicardial lead implantation is preferred despite the high rate of lead failure. The estimations of lead longevity vary widely, and seems to be difficult to predict whereas different risk factors for lead failure had been described [3][4][5][6][7][8][9][10]. In our study, we found an incidence of lead failure of 2.3% per lead per year of follow-up.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…24 Several important factors have contributed to this change. The increasing availability of pediatric-compatible transvenous devices with reduced diameter leads and smaller size generators as well as the accumulating evidence of their superiority to epicardial systems 19,[25][26][27] have led to an increasing frequency of transvenous device implants in younger pediatric patients. 28,29 In addition, of the ever-growing population of young adults with repaired or palliated CHD, a significant proportion eventually have heart rhythm complications requiring pacemaker or ICD placement.…”
Section: Discussionmentioning
confidence: 99%
“…12 The five-year survival of the conventional epicardial lead is 40-70%. 13,14 In neonates and infants with a permanent pacemakerthe occurrence of episodes of loss of consciousnessmay be due to pacemaker malfunction. 15 Follow-upchecks should be performed every 6 months inthose without symptoms; parameters of pacemakerfunction should be measured, mainly the resistanceand threshold of the atrial and ventricular leads.…”
Section: Discussionmentioning
confidence: 99%